Artistic Reflection on Artificial Intelligence Digital Painting. Issue 3 (October 2020) - Liu, Xinlu
Abstract: Material media is the premise and foundation of artistic creation. It can not only determine the classification of works of art, judge the different aesthetic styles of works of art, but also have a profound impact on the thinking and techniques of creators. With the development of computer technology and the rise of artificial intelligence, AI technology is widely used in various fields, including painting. However, the mechanical nature of AI painting's own expressive techniques limits its diversified selection of painting materials and the setting of brush parameters, and its works of art are unable to achieve the vivid and humanized expressive style of traditional painting. As a product of science and technology, with the continuous development of science and technology and the passage of time, the artistic content of works will increase. Digital technology should be regarded as a tool and means for artistic creation. Only the perfect combination of digital technology and traditional painting forms can be conducive to the innovative development of art and the sustainable development of science and technology and humanities. Based on this, this article analyzes how to dialectically look at the integration of AI technology and traditional painting art forms.